Rethinking the street. Politics, processes, and space of pedestrian- and bicycle-friendly street transformations in New York and Berlin. Straße neu Denken. Politik, Prozesse und Raum der fußgänger- und fahrradfreundlichen Transformation von Straßen in New York und Berlin. - Levels, Annika (My University, 2019)
Das Paradigma der Nachhaltigkeit hat in den letzten Jahren zunehmend Stadtentwicklung im globalen Maßstab bestimmt. Innerhalb dieses normativen Rahmens spielen Mobilität und Straßen eine zentrale Rolle mit den Zielen: Autoverkehr in Städten zu reduzieren, Fuß- und Radverkehr zu fördern und Straßen als Lebens- anstatt als Verkehrsraum zu gestalten. Stadtstraßen sind sowohl städtebauliches Gerüst, Transportinfrastruktur und öffentlicher Raum und müssen daher unterschiedliche, oft widersprüchliche und konfliktreiche Ansprüche bedienen. Um einen Wechsel hin zu "Nachhaltiger Mobilität" und "Nachhaltigen Straßen" zu erreichen, benötigen Kommunen Akteure, Prozesse und räumliche Konzepte die die gewünschte Ordnung politisch vertreten und ihre Umsetzung vorantreiben. Die damit einhergehende Veränderung der "Produktion des Raumes" führt unweigerlich zu einer Politisierung von Straßen, insbesondere im Spektrum ihrer Funktionen zwischen Verkehrsinfrastruktur und öffentlichem (Lebens-) Raum. Die Arbeit analysiert in vergleichender Perspektive, wie in New York und Berlin ein "Neudenken" von Straßen politisch vorangetrieben wurde und wie diese Prozesse Straßenraum transformiert haben. Durch die Analyse der lokalen Prozesse und die Zusammenschau von historischen, sozialwissenschaftlichen sowie planungswissenschaftlichen Perspektiven auf den städtischen Straßenraum wird in der Arbeit die Politik verdeutlicht, die die aktuelle soziale wie physische Transformation der Straße prägt. Die Politik der Straße befindet sich im Spannungsfeld von Mobilität und Lebensqualität, Ökologie und Ökonomie, zwischen globalen wie lokalen Zielen und Ansprüchen, die unter dem Label "Nachhaltigkeit" zusammengefasst werden.

On a global scale, the paradigm of Sustainability has been increasingly determining urban development. Within its normative frame, transportation and streets play crucial roles: the overall goals to reduce motorized traffic in cities, to increase the share of walking and cycling, and to turn streets into "livable" public spaces has challenged both planning processes and spatial order of urban streets. In cities, streets are simultaneously architectural baselines, transport infrastructure and one of the most important urban public spaces and therefore have to meet diverse, often conflicting and ambiguous demands. To achieve a shift towards Sustainable Mobility or Sustainable Streets on a local scale, municipalities need actors, processes and spatial concepts that politically represent the desired new order and that lead the way towards its implementation. The inherent change of the "Production of Space" has led to a politicization of urban streets between their functions as transportation infrastructure and as public space that is mostly neglected in contemporary planning literature. In a comparative gesture, the dissertation focuses on how the local governments and administrations in the case study cities New York and Berlin have politically forwarded a rethinking the streets and how this transforms the respective city's street space. While in New York the agenda has been politically initiated by the Mayor and streets are rethought through the lens of spatial quality and livability, in Berlin the transformation rather originated within the administration which mostly focuses on mobility and transport infrastructure. Hence, by analyzing the locally distinct processes of these similar, yet different case studies and by bringing together perspectives from history, the social sciences, and urban planning, this work unveils the politics of streets that nowadays shape their physical and social transformation. It will be shown, that despite the globally common paradigm, the politicization of streets has followed quite locally distinct paths and thereby produced both similar and different spaces. Contemporary politics of streets oscillate between mobility and quality-of-place, between economy and ecology, between global and local goals and demands that are subsumed under the green headline of 'sustainability'.
Keywords: Verkehr; Verkehrsplanung; Verkehrspolitik; Stadtplanung; Stadtpolitik; Stadtverkehr; Individualverkehr; Fußgängerverkehr; Fahrradverkehr; Autoverkehr; Öffentlicher Raum; Lebensraum; Straßenraum; Nutzungskonflikt; Nachhaltige Mobilität